O processo de tradução intersemiótica: do conto “As corujas”, para a cinematografia - Costa, Leandro César de Araújo da (2021)
The present work investigates the process of intersemiotic translation of the short story “As corujas” into the film version. This story by Moreira Campos was published in the book “O puxador de terço” (1969). The story was adapted by filmmaker Fred Benevides, with support from the company Alumbramento, a film production collective based in the city of Fortaleza. Through the comparison between the short story, the cinematographic script and the film, the distances and approximations between these different genres were observed. The theoretical basis used is the Semiotics proposed by Algirdas Julien Greimas. The research is also supported by the theoretical contributions of the semioticians José Luiz Fiorin and Denis Bertrand. Comparing the works with the resources of the semiotic methodology, the research allows to conclude that the cinematographic adaptation was creative in terms of expression and faithful in terms of content.